XI International Mycological Congress: report of Congress action on nomenclature proposals relating to fungi - Tom W. May; Scott A. Redhead; Lorenzo Lombard; Amy Y. Rossman (IMA Fungus)
Abstract Procedures, appointments and outcomes of the Fungal Nomenclature Session (FNS) of the 11th International Mycological Congress (IMC11) are summarized, including the composition of the Fungal Nomenclature Bureau and the Nominating Committee of the IMC. Nearly 150 mycologists attended the FNS, at which formal proposals to amend Chapter F of the International Code of Nomenclature for algae, fungi, and plants (ICN) were debated. The 18 proposals considered included 10 “from the floor”. Four proposals were withdrawn, two were sent to the Editorial Committee, five were sent to two Special-purpose Committees, four were rejected, and three were accepted (concerning: using the identifier in place of the author citation; mis-citation of identifiers; and indication of sanctioning). Proposals to amend Division III of the ICN were deemed out of scope of the FNS because they did not relate to Chapter F. The two Special-purpose Committees authorized were: “DNA Sequences as Types for Fungi” and “Names of Fungi with the Same Epithet”. Appointments made by the FNS included the Secretary of the Fungal Nomenclature Bureau for IMC12, and officers and members of the Permanent Nomenclature Committee for Fungi. Decisions and appointments of the FNS were ratified in a resolution accepted by the plenary session of the Congress.